2013
DOI: 10.1519/jsc.0b013e3182541ec6
|View full text |Cite
|
Sign up to set email alerts
|

Plyometrics' Trainability in Preadolescent Soccer Athletes

Abstract: Plyometric training (PT) is a widely used method to improve muscle ability to generate explosive power. This study aimed to determine whether preadolescent boys exhibit plyometric trainability or not. Forty-five children were randomly assigned to either a control (CG, N = 21, 10.6 ± 0.5 years; participated only in regular soccer practice) or a plyometric training group (PTG, N = 24, 10.6 ± 0.6 years; participated in regular soccer practice plus a plyometric exercise protocol). Both groups trained for 12 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
104
2
19

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(161 citation statements)
references
References 39 publications
15
104
2
19
Order By: Relevance
“…Prior research reports increases in KD of 11.5% after 7-weeks of plyometric training in female adolescent players 13 and 22.5% after 12-weeks of plyometric training in pre-adolescent boys. 24 Whilst such rapid increases could potentially be due to age and maturation, Haldankar et al 27 reported 12-weeks of RT significantly improved KD in adult amateur soccer players (11.5%). Increased strength likely contributes to an explosive knee extension motion increasing force production during the final kicking phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research reports increases in KD of 11.5% after 7-weeks of plyometric training in female adolescent players 13 and 22.5% after 12-weeks of plyometric training in pre-adolescent boys. 24 Whilst such rapid increases could potentially be due to age and maturation, Haldankar et al 27 reported 12-weeks of RT significantly improved KD in adult amateur soccer players (11.5%). Increased strength likely contributes to an explosive knee extension motion increasing force production during the final kicking phase.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 The lack of changes in the present study might also be a result of the short intervention duration. For example, Michailidis et al 24 found that only after 12-weeks of plyometric training did 30m-sprint time reduce by 3%. However, it is thought very specific training is required to optimize COD speed.…”
Section: Discussionmentioning
confidence: 99%
“…El entrenamiento de pesas y el entrenamiento pliométrico pueden provocar adaptaciones estructurales y neurales, las cuales han demostrado ser efectivas para mejorar gestos explosivos (Perez-Gomez & Calbet, 2013); este hecho podría justificar que tanto la utilización de pesas (Christou et al, 2006;Cressey et al, 2007;Jones et al, 2010;Oberacker et al, 2012), como la pliometría (Meylan & Malatesta, 2009;Michailidis et al, 2013;Sohnlein et al, 2014;Vaczi et al, 2013), sirvan como métodos de entrenamiento para provocar mejoras en la agilidad de los futbolistas. La combinación del entrenamiento de fuerza, bajo alguna de las dos modalidades indicadas anteriormente, y de resistencia (McGawley & Andersson, 2013) también ayudan a mejorar el rendimiento en agilidad.…”
Section: Discussionunclassified
“…Se ha observado que entrenar con ejercicios pliomé-tricos, durante un periodo de entre 6 y 16 semanas, permite mejorar la agilidad (Meylan & Malatesta, 2009;Michailidis et al, 2013;Sohnlein, Muller, & Stoggl, 2014;Vaczi, Tollar, Meszler, Juhasz, & Karsai, 2013).…”
Section: Entrenamiento Pliométricounclassified
See 1 more Smart Citation